THE SIGNIFICANCE OF THE EVALUATION OR ASSESSMENT FACTOR IN THE PEDAGOGICAL EVALUATION PROCESS OF WEB-BASED E-LEARNING (Proceedings of the International Conference on Future of Education, 2018)
Designing rich learning environments is an important factor in enhancing the success of web-based education. For that reason, the necessity of evaluating web-based e-Learning content is arising. The evaluation process of web-based e-Learning normally includes pedagogical evaluation and subject evaluation because e-Learning course material is a combination of course content, as well as the way it is delivered. Currently, the evaluation process is manually done by pedagogical reviewers who use various evaluation tools comprising of categories of checklists to validate the usability and validity of the e-Learning materials. Inconsistency is considered as one of the most notable challenges identified in the manual pedagogical evaluation process. A calibrated checklist was devised by considering the literature addressing this issue. This checklist was then used to automate the pedagogical evaluation process of web-based e-Learning content. Based on the checklist a questionnaire was produced and a survey conducted with pedagogical experts to identify the most important review factors. The Evaluation or Assessment review factor was highly ranked by the pedagogical reviewers in the survey. Evaluation or Assessment is essential to the learning process in web-based education and is a recognized way of measuring effective learning and assess learner’s progress. This study focused on giving comparative clarification about factors considered under Evaluation or Assessment in the manual pedagogical evaluation process of web-based e-Learning. This would help to develop a supporting tool to measure the pedagogical effectiveness of Evaluation or Assessment as the main review factor and its sub review factors.
Keywords: e-Learning; Evaluation; Assessment; Pedagogical Review